Hepatoprotective Role Of Basil Leaf Extract (Ocimum basilicum) Against the Liver of Mice (Mus musculus) Given Tuak Drink - Rudini, Mahmud; Febriyani, Uun; Candra Kurniawati, Eka; Mariska, Refi (Biosfer: Jurnal Tadris Biologi, 2025)
Basil (Ocimum basilicum) is a genus of Ocimum sp, one of the most abundant plants in Indonesia. Basil contains phenolic acids, hydrocycinate, and flavonoids that have the potential as antioxidants. The antioxidant effects of basil leaves can work effectively to protect the liver from free radicals that are generated during alcohol metabolism. This study was conducted to determine the hepatoprotective role of basil leaf extract (Ocimum basilicum) against the liver of mice (Mus musculus) given tuak drinks. This study used 25 adult male mice, aged 2 to 3 months and weighing 27 to 32 grams. There were 5 treatments and three repetitions carried out over 30 days. The extraction method is macerated, and the research design is in the form of a Complete Random Design with data analysis using One-Way Anova. The result of this study is that the administration of basil leaf extract (Ocimum basilicum) can prevent liver damage in mice (Mus musculus) caused by alcoholic beverages. Increasing the dose of basil leaf extract (Ocimum basilicum) turns out to increase the protective effect against liver damage in mice due to the administration of alcoholic beverages. The optimal dose for repairing liver damage with a dose of 900 mg/kgBB. Peran Hepatoprotektif Ekstrak Daun Kemangi (Ocimum basilicum) terhadap Hati Mencit (Mus musculus) yang diberi Minuman Tuak ABSTRAK: Kemangi (Ocimum basilicum) merupakan genus dari Ocimum sp, salah satu tumbuhan yang paling banyak dijumpai di Indonesia. Kemangi memiliki kandungan asam fenolik, hidrosisinamat, dan flavonoid yang memiliki potensi sebagai antioksidan. Efek antioksidan daun kemangi dapat bekerja efektif melindungi organ hati dari radikal bebas menangkap radikal bebas akibat metabolisme alcohol. Penelitian ini dilakukan untuk mengetahui peran hepatoprotektif ekstrak daun kemangi (Ocimum basilicum) terhadap hati mencit (Mus musculus) yang diberi minuman tuak. Penelitian ini menggunakan 25 ekor mencit jantan dewasa umur 2 sampai 3 bulan dengan bobot 27 hingga 32 gram, terdapat 5 perlakuan dan tiga kali pengulangan yang dilakukan selama 30 hari. Metode ekstraksi secara maserasi, rancangan penelitian berupa Rancangan Acak Lengkap dengan analisis data menggunakan One Way Anova. Hasil penelitian ini adalah pemberian ekstrak daun kemangi dapat mencegah kerusakan hati mencit yang disebabkan oleh minuman tuak. Peningkatan dosis ektrak daun kemangi ternyata dapat meningkatkan efek proteksi terhadap kerusakan hati mencit akibat pemberian minuman tuak. Untuk dosis optimum dalam memperbaiki kerusakan hati dengan dosis 900 Mg/KgBB